Student's Metacognitive Awareness Inventory (MAI) of English Language Education Study Program - Putri, Aulia; Eriyanti, Ribut Wahyu; Rofieq, Ainur; Hudha, Atok Miftachul (CAHAYA PENDIDIKAN, 2024)
This study aimed to identify the Metacognitive Awareness Inventory (MAI) of students in the English Education Study Program at the Faculty of Teacher Training and Education, Universitas Riau Kepulauan. The MAI consists of a self-administered questionnaire, which was administered to English Language Education students at the Faculty of Teaching and Education. This study also aimed to investigate the difference in the Metacognition Awareness levels between freshman and senior students. This study was qualitative research with 116 respondents. This study used cluster sampling which is part of probability sampling. The data were collected by using the MAI questionnaire. After that, the data were analyzed by counting the total score and percentage for each questionnaire sentence. The calculated data were explained part by part to obtain an ideal conclusion. The results exposed that the participants got the highest result in the Regulation of Cognition. For comparing Freshman and Senior Students, the Senior Students got the highest results for both Knowledge about Cognition and Regulation of Cognition.